Effect of Adding Lemongrass Stalks on Characteristics of Herbal Drink Lemongrass - Palm Sugar as a Functional Food - Putra, I Gede Arie Mahendra; Luh Putu Wrasiati; Yuarini, Dewa Ayu Anom (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2023)
Palm sugar is a product made from the sap of lontar tree flowers. Palmira Indonesia has started to develop palm sugar products in the form of powder and drinks. The addition of lemongrass stalks can be used as an alternative to improve product characteristics. This study aims to determine the effect of adding lemongrass stalks and to obtain the sensory characteristics of the lemongrass palm sugar herbal drink. This research was conducted using a completely randomized experimental design with the proportion of lemongrass stalks (0%, 5%, 10%, 15%, 20%, and 25%). The data were analyzed by analysis of variance. If significant, then proceed with Duncan's Multiple Range Test. The results showed the addition of lemongrass had a very significant effect on the scoring test of taste attributes, significantly on the hedonic test of the taste attributes and not significantly on the hedonic test of the color attribute, total acceptance, and the scoring test of the color attribute. The best treatment that can be used to make a lemongrass-sugar palm herbal drink is a 10% addition of lemongrass stalks. The panelist's acceptance of the treatment was liked for taste, color, and total acceptance attributes with the taste scoring criteria being balanced brown sugar and lemongrass and color scoring criteria being red. This treatment was also containing an antioxidant activity was 69.64% with an IC50 was 694.50 ppm, a total dissolved solid was 0.52 Brix, and a color characteristic of L* 26.9, a* 23.16, and b* 37.1 with red oxide criteria.